Tinjauan Filosofis (Pasal 2 Ayat (2) Undang-Undang Perkawinan No 1 Tahun 1974 Tentang Pencatatan Perkawinan) - Nastangin (MAHAKIM Journal of Islamic Family Law, 2018)
The registration of marriage is an administrative obligation under the provisions of ordinance number 1 of 1974 about marriage which aims to provide assurance of protection, if in the future there arises a legal act which implies the occurrence of legal consequences so that it can be proved with perfect evidence with an authentic deed as a form of certainty law. The purpose of this paper is to know about the essence of marriage registration rule article 2 section 2 of marriage ordinance number 1 of 1974. This research uses a philosophical approach that is explaining the nature and wisdom of the formal object. The conclusion of this paper is, that the registration of marriage is to provide assurance of legal protection the parties if in the future there is a problem that will result in law and to gain benefit to all people.